Multiprocessing scalable string matching algorithm for network intrusion detection system. (5th July 2019) - Hnaif, Adnan A.; Aldahoud, Ali; Alia, Mohammad A.; Al'otoum, Issa S.; Nazzal, Duaa
With high increasing speed of today's computer networks which affects the performance of security issues in terms of detection speed, the traditional security tools such as firewall is insufficient to protect the networks from external threads. Intrusion detection systems (IDS) are one of the most reliable tools that can be used to monitor all the network traffic to identify unauthorised usage of computer system networks. In this paper, we have proposed a scalable string matching algorithm based on network IDS (NIDS) to enhance the speed of NIDS detection engine, which called multiprocessing scalable string matching algorithm for network intrusion detection system (MSNIDS). The MSNIDS implemented by using enhanced weighted exact matching algorithm (EWEMA) in both sequential and parallel processing. The MSNIDS based on EWEMA can be achieved more than 89% in sequential processing time compared with WEMA, and 86% in parallel processing time compared with sequential matching processing.